Effect of Extrusion on the Functional Properties and Bioactive Compounds of Tamarind (Tamarindus indica L.) Shell - Dalia Samanta Aguilar-Avila; Hector Eduardo Martinez-Flores; Eduardo Morales-Sanchez; Rosalía Reynoso-Camacho; Ma. Guadalupe Garnica-Romo (Polish Journal of Food and Nutrition Sciences)
The food-use of the tamarind ( Tamarindus indica L.) fruit produces shell and seeds as by-products. In this work, the effects of the tamarind shell moisture content and the temperature of their extrusion on the dietary fiber content and physiochemical properties, such as water absorption capacity (WAC), oil absorption capacity (OAC), and glucose dialysis retardation index (GDRI) of the extrudates, were estimated. Moreover, the effects of the extrusion variables on the total phenolic and total flavonoid contents and on the antioxidant capacity of the tamarind shell were evaluated. The dry powdered tamarind shell was conditioned to have 32 or 39 g of water per 100 g of shell, prior to being subjected to extrusion. Subsequently, the conditioned samples were processed at 90°C, 100°C and 110°C in a single screw extruder. A non-extruded tamarind shell was taken as a control. The extrusion resulted in a 138.3% increase in the soluble dietary fiber content, along with 40.3% and 18.4% reductions of total phenolic and total flavonoid contents, respectively. The antioxidant capacity of the tamarind shell with moisture content of 32 g/100 g extruded at 100°C and 110°C was similar to that of non-extruded material. Moreover, the extruded products had the higher OAC compared to that of the control and they displayed an excellent response with regard to controlling the GDRI. The extrusion advantageously modified properties of the tamarind shell particularly when material with a moisture content of 32 g/100 g at 100°C was processed.